Tolerability, safety, and pharmacokinetics of a single intravenous administration of a novel recombinant humanized anti-interleukin-6 receptor monoclonal antibody in healthy Chinese volunteers - Jiang, Xin; Lin, Pingping; Sun, Feifei; Xu, Yi; Tao, Ye; Shi, Ping; Liu, Yanping; Li, Xin; Liu, Shuqin; Gao, Xiaomeng; Wang, Chenjing; Cao, Yu (Frontiers in Pharmacology, 2024)
Aim: VDJ001 is a novel recombinant humanized monoclonal antibody against anti-interleukin-6 receptor. As an analogue of tocilizumab, it exhibited improved affinity and in vitro activity. Based on preclinical studies, a first-in-human clinical study was conducted to evaluate the safety, tolerability and pharmacokinetics of VDJ001. Methods: This is a single-center, randomized, double-blinded, placebo-controlled phase I dose-escalation study conducted in healthy Chinese volunteers. 4 cohorts were designed with dosage range from 1 to 8 mg/kg. There were equal numbers of female and male volunteers in each cohort. Enrolled subjects randomly received a single intravenous administration of VDJ001 or placebo (VDJ001: placebo= 4:1 in both female and male). Three sentinel volunteers in the 1mg/kg cohort firstly administrated, and the treatment of the other 7 volunteers was carried out after a safety assessment on D15. The following cohort was conducted only when the safety profile was evaluated acceptable on D29 of the previous cohort. Samples for pharmacokinetics, pharmacodynamics and immunogenicity were collected at specified time points and analyzed through validated methods. Adverse events and results of examination and laboratory were analyzed to assess the safety profile. Results: All cohorts were carried out according to the protocol. With the escalation of dosage, Cmax increased linearly, AUC0-t and AUC0-∞ increased in a nonlinear manner, while clearance decreased andt1/2 prolonged . Six volunteers who received VDJ001 were tested ADA-positive, among whom 1 participant was Nab-positive on D57. One volunteer in the placebo group was ADA-positive but Nab-negative. CRP concentrations were not found correlated with dosage. Both IL-6 and sIL-6R concentrations increased after administration of VDJ001. All adverse events were mild to moderate in severity. No serious adverse events were reported in this study. No unexpected or clinically significant safety issues were found. Conclusion: Safety and tolerability of VDJ001 are acceptable with a single intravenous dosage of 1~8mg/kg. Further clinical trials are warranted.